Combined use of two separate but protective vaccine antigens provides protection against Taenia ovis infection in lambs in the presence of protective maternal antibody. Issue 15 (8th April 2021) - Harrison, G.B.L.; Heath, D.D.; Robinson, C.M.; Lawrence, S.B.; Dempster, R.P.; Gauci, C.G; Lightowlers, M.W.; Rickard, M.D.
Highlights: Experiments were undertaken to investigate protection of young lambs against Taenia ovis infection. Three different, protective, recombinant antigens from T. ovis were used. Lambs born from vaccinated dams were protected by maternal antibody. Specific colostrum-derived antibody inhibited active immunization of lambs using the same antigen. Lambs were fully protected after vaccination of dams and lambs with different antigens. Abstract: Three recombinant Taenia ovis antigens (To45, To16, To18) each induce protective immunity in lambs or ewes against infection with T. ovis metacestodes. The degree and duration of immunity were assessed in lambs born from vaccinated ewes. Treatment group sizes varied, typically not fewer than 5 animals per group. Ewes were immunised with one T. ovis recombinant protein prior to lambing and the degree and duration of passive immunity in their lambs was assessed by challenge infection up to 18 weeks. Lambs were fully protected up to 6 weeks of age but immunity waned from 6 to 12 weeks and there was no protection when lambs were challenged at 15 weeks. Immunisation of lambs with the homologous recombinant antigen was not effective when vaccinations were given when maternal antibody was high. Lambs were effectively immunised in the presence of passively protective antibody when vaccinated with an antigen that was different to that given to ewes. Vaccination of lambs with a combination of two proteins, To16 and To18, was more effective than giving these single antigens and gave a significant reduction of cyst numbers when lambs were challenged 12 months after immunisation. These results indicate that the use of combinations of T. ovis recombinant antigens could enable complete protection of lambs against infection, if a delivery system becomes available that will maintain antibody at protective levels for 12 months. Alternatively, a third injection given at 6 months may promote the anamnestic response to give long lasting protection.